Integrasi Budaya Lokal dalam Praktik Keagamaan Perspektif Hukum Islam: Studi Kesenian Dambus dalam Penggalangan Dana Pembangunan Masjid di Pangkalpinang - Ismanto, Reno; Amin, Muhammad (LP2M IAIN Syaikh Abdurrahman Siddik Bangka Belitung, 2023)
Local tradition in its various forms was practiced by the people of the archipelago, before the arrival of Islam. In its development there was an assimilation between local traditions and religious practices of the Muslim community in Indonesia. This study intends to reveal how the process of assimilation of local wisdom into the religious practices of Muslim communities in Indonesia, especially in Bangka Belitung. This study uses qualitative research methods with observation instruments and interviews with several informants, namely religious and community leaders. This study finds that local wisdom that is incorporated into religious practice, such as the Dambus tradition, is driven by the motivation to maintain the traditions or heritage of predecessors. On the other hand, this effort intends to show that religious values can still be practiced without having to lose identity and culture. And Based on Islamic law, this form of religious practices is not contrary with the rules dan principles of Islam.